Cryptococcal 3-Hydroxy Fatty Acids Protect Cells Against Amoebal Phagocytosis - Madu, Uju L.; Ogundeji, Adepemi O.; Mochochoko, Bonang M.; Pohl, Carolina H.; Albertyn, Jacobus; Swart, Chantel W.; Allwood, J. William; Southam, Andrew D.; Dunn, Warwick B.; May, Robin C.; Sebolai, Olihile M. (Frontiers in Microbiology, 2015)
We previously reported on a 3-hydroxy fatty acid that is secreted via cryptococcal capsular protuberances - possibly to promote pathogenesis and survival. Thus, we investigated the role of this molecule in mediating the fate of Cryptococcus (C.) neoformans and the related species C. gattii when predated upon by amoebae. We show that this molecule protects cells against the phagocytic effects of amoebae. C. neoformans UOFS Y-1378 (which produces 3-hydroxy fatty acids) was less sensitive towards amoebae compared to C. neoformans LMPE 046 and C. gattii R265 (both do not produce 3-hydroxy fatty acids) and addition of 3-hydroxy fatty acids to C. neoformans LMPE 046 and C. gattii R265 culture media, causes these strains to become more resistant to amoebal predation. Conversely, addition of aspirin (a 3-hydroxy fatty acid inhibitor) to C. neoformans UOFS Y-1378 culture media made cells more susceptible to amoebae. Our data suggest that this molecule is secreted at a high enough concentration to effect intracellular signalling within amoeba, which in turn, promotes fungal survival.